2009
DOI: 10.5539/ijef.v1n1p103
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Human Resource Management and Firm Performance in Malaysia

Abstract: Drawing upon resource based theory which explains human capital as the key resource for the firms' development, this paper hypothesized that the human resource management (HRM) was anchored on firm performance. HRM were conceptualized as 4-and unidimensional constructs, respectively. The main thrust of the paper is to assess the impact of HRM on firm performance. The research uses a sample of 85 firms surveyed in Sarawak, Malaysia. The findings suggested that incentives and information technology are positivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Three EO dimensions (proactivity, risk-taking, and innovation) had a positive effect on the companies' performance (Keh et al, 2007). In addition, technological innovation, competitiveness, and proactivity were found to substantially impact a firm's performance (Lo, 2009). Such characteristics are associated with improved firm performance in today's business environments, where product and business model life cycles are shortened (Hamel, 2000).…”
Section: Firm Performancementioning
confidence: 99%
“…Three EO dimensions (proactivity, risk-taking, and innovation) had a positive effect on the companies' performance (Keh et al, 2007). In addition, technological innovation, competitiveness, and proactivity were found to substantially impact a firm's performance (Lo, 2009). Such characteristics are associated with improved firm performance in today's business environments, where product and business model life cycles are shortened (Hamel, 2000).…”
Section: Firm Performancementioning
confidence: 99%
“…A study by Nasip et al (2015) shows that technology is important for the sustainability of SMEs and it has a direct effect on the performance of the SMEs. Lo et al (2009) studied 85 manufacturing companies located in Sarawak, Malaysia and concluded that there is a positive and significant relationship between a firm's performance and information technology. However, another study which surveyed 383 SMEs indicated that SMEs owners IT skills levels are low and usage of the internet in their workplace is rare (Hashim, 2015).…”
Section: Information Technologymentioning
confidence: 99%